Finite element analysis of excavation in residual soils - Andy (2016)
In this study, the finite element software PLAXIS 2D software is used to study the behavior of deep excavations in deposits of Bukit Timah Granite. Analyses were carried out to assess the parameters that influence the performance of the excavation system such as the diaphragm wall deflection and bending moment as well as the forces in the supporting struts. The parameters considered include the groundwater level, permeability of soils, Young Modulus, soil cohesion and friction angle and also wall stiffness. A total of sixteen cases were considered. The results indicate that in most cases, wall deflections and maximum bending moment have a strong correlation to the soil’s elastic modulus and friction angle where an increase in the parameters would result in decreasing moment and deflection. In addition, maximum struts forces are observed to correlate very well to these parameters except for the first level struts. Due to kick back of the wall, the first level struts could be in tension instead of compression state. This is especially observed in cases with weaker parameters overall. The results obtained in this study demonstrated the sensitivity of the soil properties to the safety of the excavation, which calls for thorough soil investigation in any major excavation.